Impact Of Goal Orientation, Personality Types And Campus Climate At Uin Syarif Hidayatullah Jakarta Nursing Student’s Work Readiness - Citra Kemilau Ramadhania; Mulia Sari Dewi (‎‎‎TAZKIYA Journal of Psychology, 2017)
The rapid development of science and technology resulted in increasingly tight competition on obtaining work. Moreover, with the implementation of the trade zone of the Asean Economic Community (AEC) currentlyits the realization of the Asia free market. There are eight professions involved in MEA competition, among which the the field of nursing, so the work readiness become important that a student should have when facing the world of work. This study was conducted to determine the influence of significants goal orientation, personality type, and campus climate on work readiness. Subjects in this study is 5 to 9 semester student of nursing and 1 and 3 semester of UIN Syarif Hidayatullah nurses profession student amounted to 151 are taken by purposive sampling technique. The results show that there an influence of goal orientation, personality type, and campus climate on work readiness is significant with the proportion of the variance is 63.6%. The hypothesis minor test show that emotionality, extraversion, conscientiousness, and teaching learning have a significant influence on work readiness. While learning goals, performance goals, honesty-humility, agreeableness, openness to experience, safety, interpersonal relations and the institutional environment have no significant effect.Suggestions for subsequent research in order to use other variables in order to enrich this study.   DOI:10.15408/tazkiya.v22i2.8399